Exploring the ability of triple quadrupole inductively coupled plasma mass spectrometry for the determination of Pu isotopes in environmental samples. Issue 11 (14th October 2021) - Bu, Wenting; Gu, Mei; Ding, Xiaotong; Ni, Youyi; Shao, Xuepeng; Liu, Xuemei; Yang, Chuting; Hu, Sheng
Abstract : Expanding the ability of ICP-MS/MS for the determination of Pu isotopes in environmental samples. Abstract : The monitoring of Pu isotopes in environmental samples was essential for radioactive assessment and tracing the geochemical processes. Triple quadrupole inductively coupled plasma mass spectrometry (ICP-MS/MS) has shown strong ability for long-half lived radionuclide analysis with respect to interference removal capability. In this study, we explored the ability of ICP-MS/MS for the ultra-trace determination of Pu isotopes in environmental samples. The Pu sensitivity was improved more than 10 times by using an APEX-Ω high efficiency sample introduction system. The absolute detection limits for 239 Pu and 240 Pu were about 0.13 fg (0.0003 mBq) and 0.08 fg (0.0007 mBq), respectively. After the introduction of NH3 and He into the reaction cell with appropriate gas flow rates, the U hydride removal capability (UH + /U + : 1.2 × 10 −6 ) was improved, while the Pu sensitivity (7400 cps ppt −1 ) was still remarkable. A simple one stage chromatographic separation method with a suitable Pu eluent was established for the separation of Pu from soil and sediment samples. The sample matrix effect and the UH + interference were eliminated with the coupling of the separation procedure and the ICP-MS/MS detection method. Several reference materials were analyzed for the validation of the method. The results revealed that our method was suitable for the determination of Pu isotopes in environmental samples.